Establishment of an indirect immunofluorescence assay for the detection of African swine fever virus antibodies - Wan Wang; Zhenjiang Zhang; Weldu Tesfagaber; Jiwen Zhang; Fang Li; Encheng Sun; Lijie Tang; Zhigao Bu; Yuanmao Zhu; Dongming Zhao (Journal of Integrative Agriculture, 2024)
African swine fever (ASF) continues to cause enormous economic loss to the global pig industry. Since there is no safe and effective vaccine, accurate and timely diagnosis of ASF is essential to implement control measures. Indirect immunofluorescence assay (IFA) is a gold standard serological method recommended by the World Organization for Animal Health (WOAH). In this study, we used primary fetal kidney cells to establish a wild boar cell line (BK2258) that supported the efficient replication of ASF virus (ASFV) SD/DY-I/21 and showed visible cytopathic effect (CPE). Moreover, using BK2258, we established a sensitive and specific IFA for ASFV antibody detection. To standardize and evaluate the performance of this assay, we used serum samples from pigs infected with the low virulent genotype I SD/DY-I/21 and genotype II HLJ/HRB1/20, and immunized with the vaccine candidate HLJ/18-7GD, field samples, and negative serum samples. The IFA reacted with the ASFV-positive sera and displayed bright fluorescence foci. There was no non-specific green fluorescence due to cellular senescence or other cell damage-causing factors. Compared to a commercial indirect enzyme-linked immunosorbent assay (iELISA), ASFV antibodies were detected 1–4 days earlier using our IFA. The detection limits of the IFA and iELISA for the same ASFV-antibody positive serum samples were 1:25,600 and 1:6,400, respectively, indicating that the IFA is more sensitive than iELISA. The newly established IFA was highly specific and did not cross-react with sera positive for six other important porcine pathogens (i.e., Classical swine fever virus (CSFV), Porcine reproductive and respiratory syndrome virus (PRRSV), Porcme circovirus type 2 (PCV2), Pseudorabies virus (PRV), Foot-and-Mouth disease virus type O (FMDV/O), and Porcine epidemic diarrhea virus (PEDV)). This study thus provides a sensitive, specific, and reliable detection method that is suitable for the serological diagnosis of ASF.